Biomimetic Design and Assessment via Microenvironmental Testing: From Food Packaging Biomaterials to Implantable Medical Devices - Diana V. Portan; Athanasia Koliadima; John Kapolos; Leonard Azamfirei (Biomimetics)
Biomaterials and biomedical devices interact with the human body at different levels. At one end of the spectrum, medical devices in contact with tissue pose risks depending on whether they are deployed on the skin or implanted. On the other hand, food packaging and associated material technologies must also be biocompatible to prevent the transfer of harmful molecules and contamination of food, which could impact human health. These seemingly unlinked domains converge into a shared need for the elaboration of new laboratory evaluation protocols that consider recent advances in biomaterials and biodevices, coupled with increasing legal restrictions on the use of animal models. Here, we aim to select and prescribe physiologically relevant microenvironment conditions for biocompatibility testing of novel biomaterials and biodevices. Our discussion spans (1) the development of testing protocols according to material classes, (2) current legislation and standards, and (3) the preparation of biomimetic setups that replicate the microenvironment, with a focus on the multidisciplinary dimension of such studies. Testing spans several characterization domains, beginning with chemical properties, followed by mechanical integrity and, finally, biological response. Biomimetic testing conditions typically include temperature fluctuations, humidity, mechanical stress and loading, exposure to body fluids, and interaction with multifaceted biological systems.